Tropical sea surface temperatures for the past four centuries reconstructed from coral archives. (18th March 2015) - Tierney, Jessica E.; Abram, Nerilie J.; Anchukaitis, Kevin J.; Evans, Michael N.; Giry, Cyril; Kilbourne, K. Halimeda; Saenger, Casey P.; Wu, Henry C.; Zinke, Jens
Abstract Most annually resolved climate reconstructions of the Common Era are based on terrestrial data, making it a challenge to independently assess how recent climate changes have affected the oceans. Here as part of the Past Global Changes Ocean2K project, we present four regionally calibrated and validated reconstructions of sea surface temperatures in the tropics, based on 57 published and publicly archived marine paleoclimate data sets derived exclusively from tropical coral archives. Validation exercises suggest that our reconstructions are interpretable for much of the past 400 years, depending on the availability of paleoclimate data within, and the reconstruction validation statistics for, each target region. Analysis of the trends in the data suggests that the Indian, western Pacific, and western Atlantic Ocean regions were cooling until modern warming began around the 1830s. The early 1800s were an exceptionally cool period in the Indo‐Pacific region, likely due to multiple large tropical volcanic eruptions occurring in the early nineteenth century. Decadal‐scale variability is a quasi‐persistent feature of all basins. Twentieth century warming associated with greenhouse gas emissions is apparent in the Indian, West Pacific, and western Atlantic Oceans, but we find no evidence that either natural or anthropogenic forcings have altered El Niño–Southern Oscillation‐related variance in tropical sea surface temperatures. Our marine‐based regional paleoclimate reconstructions serve as benchmarks against which terrestrial reconstructions as well as climate model simulations can be compared and as a basis for studying the processes by which the tropical oceans mediate climate variability and change.